2019
DOI: 10.1152/ajprenal.00089.2019
|View full text |Cite
|
Sign up to set email alerts
|

Peptidyl arginine deiminase-4 exacerbates ischemic AKI by finding NEMO

Abstract: Peptidyl arginine deiminase-4 (PAD4) catalyzes the conversion of peptidylarginine residues to peptidylcitrulline. We have previously shown that kidney ischemia-reperfusion (I/R) injury increases renal proximal tubular PAD4 expression and activity. Furthermore, kidney PAD4 plays a critical role in ischemic acute kidney injury (AKI) by promoting renal tubular inflammation, neutrophil infiltration, and NF-κB activation. However, the mechanisms of PAD4-mediated renal tubular inflammation and NF-κB activation after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Therefore, the favorable effect of the NBD peptide is not only due to the inhibition of proinflammatory NF-κB signaling, but also through the restoration of redox balance. Our findings in the context of diabetes-induced kidney disease are consistent with other studies emphasizing the powerful therapeutic effects of different NBD-based strategies in preclinical models of Duchenne muscular dystrophy [28], Parkinson's disease [50], arthritis [27], breast cancer [31] and ischemic acute kidney injury [51]. A recent phase I trial of NBD peptide administration in dogs with large B-cell lymphoma demonstrated safety and efficacy [32], offering hope for translation to human disease.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the favorable effect of the NBD peptide is not only due to the inhibition of proinflammatory NF-κB signaling, but also through the restoration of redox balance. Our findings in the context of diabetes-induced kidney disease are consistent with other studies emphasizing the powerful therapeutic effects of different NBD-based strategies in preclinical models of Duchenne muscular dystrophy [28], Parkinson's disease [50], arthritis [27], breast cancer [31] and ischemic acute kidney injury [51]. A recent phase I trial of NBD peptide administration in dogs with large B-cell lymphoma demonstrated safety and efficacy [32], offering hope for translation to human disease.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, we found that PAD4 preferentially citrullinates inhibitor of κB (IκB) kinase-γ (IKK-γ, also known as NFκB essential modulator or NEMO) over other IKK subunits, IKK-α or IKK-β. Inhibition of NEMO by NEMO-binding peptide attenuated PAD4-mediated exacerbation of ischemic AKI, apoptosis, and inflammation, suggesting that NEMO citrullination is a central mediator of both PAD4 and P 2 X 7 -mediated ischemic AKI [83]. We summarize our previous and current findings and proposed a detailed mechanism of PAD4-mediated renal tubular inflammation and exacerbation of ischemic AKI in Fig.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 64%
“…In addition, we provided updated potential therapeutic targets, such as TLRs (TLR2/4/9), ARs, and PAD4 for the prevention or treatment of ischemic AKI. Moreover, we proposed mechanisms of ischemic AKI-induced liver, intestine, and kidney dysfunction and systemic inflammation mainly mediated by Paneth cell degranulation (Table 1) [54,55,63,67,6974,78,79,82,83,86]. Although progress for this disease treatment and prevention is being made on multiple fronts, many hurdles have to be overcome because the mortality and morbidity of this disease only slightly improved after 4 decades.…”
Section: Discussionmentioning
confidence: 99%
“…PAD4 has also been found, in patients, to be involved in the pathogenesis of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) [ 127 ]. Furthermore, neutrophil-derived PAD4 has been linked to ischaemia–reperfusion kidney injury [ 128 ], where PAD4 has been found to promote renal tubular inflammation, neutrophil infiltration, and NF-κB activation [ 129 ]. In our current study, we did observe some changes in PAD expression in SARS-CoV-2-infected kidney biopsies, including elevation of PADI4, PADI1, PADI3 and PADI6 mRNA in some of the five cases.…”
Section: Discussionmentioning
confidence: 99%